We Have Trust Issues - Mapaling, Curwyn; Mukadam, Nadia; Hamukuaya, Hashali (Critical Studies in Teaching and Learning, 2025)
This poetic inquiry explores the complex dynamics of trust within the context of higher education, particularly focusing on the collective experiences of marginalised communities. Drawing from the themes of the special issue "Reimagining Trust in Higher Education" in the journal Critical Studies in Teaching and Learning (CriSTaL), the poem grapples with the deep-seated mistrust that stems from historical and ongoing injustices, such as colonialism, apartheid, and systemic inequality. Through a powerful and evocative use of the collective voice, the poem highlights the shared struggles and resilience of those fighting for social justice, decolonisation, and equity in academia. It interrogates the hollow promises of trust from institutions that have perpetuated harm and exclusion, while also acknowledging the transformative potential of collective action and self-determination. By weaving together personal and political narratives, the poem invites readers to reflect on the urgent need to cultivate genuine trust, healing, and solidarity within higher education. It challenges us to confront the depths of institutional betrayal and to imagine new possibilities for building a more just and inclusive academic landscape. Situated within the broader discourses of critical pedagogy, decolonial praxis, and social justice education, this poetic inquiry contributes to the ongoing conversations about reimagining trust in higher education. It offers a creative and embodied approach to engaging with the complexities of trust, trauma, and resistance, and calls for a radical transformation of the structures and relationships that shape our educational spaces.